Pengaruh Kualitas Layanan Customer Service Terhadap Kepuasan Pengunjung Di Solo Safari - Tamarin Lintang Arafah; Emmelia Nadira Satiti; Bartolomeus Herawan Mintardjo (Journal of Innovative and Creativity, 2025)
The purpose of this study was to determine the effect of customer service quality on visitor satisfaction at Solo Safari. This study employed descriptive qualitative techniques. Data collection included observation, interviews, and documentation. A random sample of ten Solo Safari visitors was selected and analyzed using data triangulation techniques. The data obtained indicated that customer service quality, including tangibles, reliability, responsiveness, assurance, and empathy, is a key service quality, as evidenced by the satisfaction of visitors who have visited Solo Safari multiple times. The results of this discussion indicate that customer service quality significantly influences visitor satisfaction at Solo Safari. This satisfaction stems not only from the facilities available, but also from the direct interaction between visitors and customer service staff.